Neuron-Glia Interaction as a Possible Glue to Translate the Mind-Brain Gap: A Novel Multi-Dimensional Approach Toward Psychology and Psychiatry - Kato, Takahiro A.; Watabe, Motoki; Kanba, Shigenobu (Frontiers in Psychiatry, 2013)
Neurons and synapses have long been the dominant focus of neuroscience, thus the pathophysiology of psychiatric disorders has come to be understood within the neuronal doctrine. However, the majority of cells in the brain are not neurons but glial cells including astrocytes, oligodendrocytes and microglia. Traditionally, neuroscientists regarded glial functions as simply providing physical support and maintenance for neurons. Thus, in this limited role glia had been long ignored. Recently, glial functions have been gradually investigated, and increasing evidence has suggested that glial cells perform important roles in various brain functions. Digging up the glial functions and further understanding of these crucial cells, and the interaction between neurons and glia may shed new light on clarifying many unknown aspects including the mind-brain gap, and conscious-unconscious relationships. We briefly review the current situation of glial research in the field, and propose a novel translational research with a multi-dimensional model, combining various experimental approaches such as animal studies, in vitro & in vivo neuron-glia studies, a variety of human brain imaging investigations, and psychometric assessments.